Extra Virgin Olive Oil Modulates Vasodilator Enzyme Level by Repairing Angiogenesis Function in Rat Model of Preeclampsia - Yulia Silvani; Agnestia Naning Dian Lovita; Afniari Maharani; I Wayan Arsana Wiyasa; Hidayat Sujuti; Retty Ratnawati; Tri Yudani Mardining Raras (Tehran University of Medical Sciences, 2020)
Objective: This study aimed to determine the effect of Extra Virgin Olive Oil (EVOO) on vasodilator enzyme by repairing angiogenic function in rat model of preeclampsia. Materials and methods: This research consisted of five groups; negative control (normal pregnant rats) group, positive control (preeclampsia rat model) group, preeclampsia rat model groups given EVOO in 3 different doses (0.5 ml/day, 1 ml/day, and 2 ml/day, respectively). Blood pressure measurements were carried out on day 12, 15, and 19 of pregnancy. After the rats were sacrificed, the placentas were collected to determine endothelial Nitric Oxide Synthase (eNOS) level of maternal plasma to determine soluble Fms-like Tyrosine Kinase 1 (sFlt-1) and Vascular Endothelial Growth Factor (VEGF) level. Results: There were significant higher sFlt-1 level (p < 0.001), lower VEGF level (p = 0.009), and lower eNOS level (p = 0.034) between negative and positive control groups. After EVOO administration, sFlt-1 level was lower in dose 1 and 2 groups but higher in dose 3 group in accordance with VEGF and eNOS levels that were increasing both in dose 1 and dose 2 groups but decreasing in dose 3. There were significant differences between positive control and dose 1 (p = 0.015) and dose 2 (p = 0.001) in sFlt-1 level. None of all dose groups were statistically different with positive control group in VEGF level (dose 1 p = 0.601; dose 2 p = 0.297; dose 3 p = 0.805). eNOS levels of all dose groups were statistically different from that of the positive control group (dose 1 p = 0.014; dose 2 p = 0.001; dose 3 p = 0.024). Conclusion: Administration of EVOO modulates eNOS as vasodilator enzyme by repairing the angiogenic function indicated by decreased sFlt-1 level and increased VEGF in rat model of preeclampsia.